(untitled) (Al-Qamar, 2022)
This article studies the preface of “Tuhfat al-Ahwadhī”, a well- commentary on “Jāmiʻ Tirmidhī” by Mawlānā Abdur Rahmān MubārakPūrī, a renowned religious scholar of the sub-continent. It finds that various topics related to Ḥadīth have been commented in a beautiful and valuable way by the learned commentator. Various terms used in the books of hadīths, such as the beginning of the commentary with Bismillāh and Alḥamdulillāh, the discussions related to genealogy, the means and conducts of receiving and preserving traditions, the levels of the means and ways, have been discussed nicely and very comprehensive way. The learned commentator has quoted the sayings of beloved teacher and the early and late scholars in the course of all these discussions. Thus “Tuhfat al-Ahwadhī” is the best and comprehensive commentary on “Jāmiʻ Tirmidhī” that contains immense knowledge and guidance for students and scholars of ḥadīth.